Comparison of code-mixing between English and Mandarin speaking young Chinese adults in Malaysia - Ng, Man Ling (2018)
Code-mixing is a sociolinguistic phenomenon in Malaysia where people integrate words of other languages into their dominant language. Chinese Malaysians can be generally divided into two sub-groups: English and Mandarin speaking Chinese. Previous studies mostly have focused on code-mixing between different ethnic groups and generations, as well as in second language situations. However, there is a lack of information on code-mixing among Chinese Malaysians with different language dominance.